Evaluación de diferentes niveles de fitasa (Myo-inositol hexafosfato fosfohidrolasas) en dietas para cerdos de inicio de 49 a 70 días de edad - Dueñas Veliz, Pedro Javier (2024)
This research aimed to assess productive and health parameters in early-stage pigs with varying levels of phytase (myo-inositol hexaphosphate phosphohydrolases). Sixteen pigs were divided into 4 treatments with different phytase concentrations and a control (T0=0FTU/kg, T1=500FTU/kg, T2=1600 FTU/kg, and T3=2500 FTU/kg). Blood samples were collected for health assessments at the beginning and end of the study. Productive parameters measured included initial weight, weekly weight, final weight, weekly weight gain, and feed conversion. Health parameters measured included hematocrit, hemoglobin, platelets, and leukocytes. A completely randomized design was applied, and variables showing significant differences (P<0.05) underwent Tukey's test at a 95% confidence level. There were no significant differences in pig weight between treatments, but differences were observed in weight gain and feed conversion. T3 was statistically superior to T0 in weight gain and feed conversion, numerically surpassing other treatments. Regarding health parameters, no significant differences (P>0.05) were found among treatments, and they fell within reference ranges. In the cost-benefit analysis, T3 showed superiority, exhibiting a 30% benefit compared to the investment. In conclusion, the inclusion of phytase at levels of 2500FTU/kg improves productive parameters and benefit estimation compared to no addition or low phytase inclusions.